2016
DOI: 10.1111/hel.12302
|View full text |Cite
|
Sign up to set email alerts
|

Increased Exhaled 8‐Isoprostane and Interleukin‐6 in Patients with Helicobacter pylori Infection

Abstract: H. pylori infection causes an asymptomatic airway inflammation which can be detected by exhaled breath condensate. The clinical importance of this inflammation remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 32 publications
(32 reference statements)
0
12
1
1
Order By: Relevance
“…The existing literature shows that patients with NAFLD have higher BUN values 61 . In summary, a previous study showed that in NAFLD patients, an elevated GGT concentration was associated with an increase in the risk of CKD among nondiabetic, non-hypertensive Korean men, regardless of whether metabolic syndrome was present 62 . However, our study supports the notion that ALD and H. pylori infection specifically influence BUN levels.…”
Section: Discussionmentioning
confidence: 74%
“…The existing literature shows that patients with NAFLD have higher BUN values 61 . In summary, a previous study showed that in NAFLD patients, an elevated GGT concentration was associated with an increase in the risk of CKD among nondiabetic, non-hypertensive Korean men, regardless of whether metabolic syndrome was present 62 . However, our study supports the notion that ALD and H. pylori infection specifically influence BUN levels.…”
Section: Discussionmentioning
confidence: 74%
“…In addition to urinary samples [133135], other noninvasive and low-cost tools for the screening of oxidative stress, such as salivary [136138] or exhaled breath [139141] analysis, have been proposed. However, it has been reported that creatinine urinary markers are not suitable in patients with impaired renal function [135].…”
Section: Markers Based On Ros-induced Modificationsmentioning
confidence: 99%
“…34 Reports have confirmed that H. pylori-induced chronic inflammation may enhance the production of IL-6, TNFα, and CRP. 35,36 These proinflammatory cytokines would stimulate a series of kinases like JNK, and IKK/NF-kB, leading to enhance IR by suppression of the autophosphorylation of the tyrosyl of the insulin receptor substrate (IRS)-1 37 or upregulating Ser phosphorylation. 38 A recent study was in agreement with our finding that H. pylori infection was related to increased serum leptin.…”
Section: Data From a Follow-up Assessment Extra 3 Months After Compmentioning
confidence: 99%